"Think Before You Click. Post. Type." Lessons learned from our University Cyber Security Awareness Campaign - Rachael L. Innocenzi; Kaylee Brown; Peggy Liggit; Samir Tout; Andrea Tanner; Theodore Coutilish; Rocky J. Jenkins (Journal of Cybersecurity Education, Research & Practice)
This article discusses the lessons learned after implementing a successful university-wide cyber security campaign. The Cyber Security Awareness Committee (CyberSAC), a group comprised of diverse units across campus, collaborated together on resources, talent, people, equipment, technology, and assessment practices to meet strategic goals for cyber safety and education. The project involves assessing student learning and behavior changes after participating in a Cyber Security Password Awareness event that was run as a year-long campaign targeting undergraduate students. The results have implications for planning and implementing university-wide initiatives in the field of cyber security, and more broadly, higher education at large.